1982
DOI: 10.1002/ajh.2830130304
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pilot study of a cytotoxic antiserum in myeloblastic leukemia

Abstract: A large dose of equine antilymphocytic globulin (ALG, 120 mg/kg/day) was given intravenously to four patients with myeloblastic leukemia. Leukemic myeloblasts from each patient were lysed by the ALG in vitro, in the presence of the same patient's serum complement. In each patient, ALG infusion was followed by a reduction in the count of circulating leukemic myeloblasts, and a fall in the serum levels of C3 and C4 complement. It is likely that complement-mediated lysis of circulating leukemic myeloblasts occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Using a ^'Cr release assay (Sanderson 1964), the present author showed that equine ALS manufactured by the Hoechst-Behringwerke Pharmaceutical Company had a similar cytotoxic effect on normal human blood mononuclear cells and leukemic myeloblasts in the presence of human complement (Figure 1). When this type of ALS was given intravenously to four patients with myeloblastic leukemia, in a dose of 120 mg horse Ig/kg body weight, a transient reduction in the peripheral blood myeloblast count was observed in each patient, and the patients' serum C3 and C4 complement levels also fell (Heyworth 1982, Heyworth et al 1982. It is likely that complement-mediated destruction of circulating leukemic myeloblasts occurred in these patients as a result of ALS administration.…”
Section: Lymphoma and Leukemiamentioning
confidence: 98%
See 1 more Smart Citation
“…Using a ^'Cr release assay (Sanderson 1964), the present author showed that equine ALS manufactured by the Hoechst-Behringwerke Pharmaceutical Company had a similar cytotoxic effect on normal human blood mononuclear cells and leukemic myeloblasts in the presence of human complement (Figure 1). When this type of ALS was given intravenously to four patients with myeloblastic leukemia, in a dose of 120 mg horse Ig/kg body weight, a transient reduction in the peripheral blood myeloblast count was observed in each patient, and the patients' serum C3 and C4 complement levels also fell (Heyworth 1982, Heyworth et al 1982. It is likely that complement-mediated destruction of circulating leukemic myeloblasts occurred in these patients as a result of ALS administration.…”
Section: Lymphoma and Leukemiamentioning
confidence: 98%
“…It was concluded that lymphocytotoxic antibody was rapidly removed from the patients' sera following ALS administration, by binding to circulating lymphocytes (Heyworth 1981). In a clinical study of the effect of horse ALS in myeloblastic leukemia (Heyworth 1982, Heyworth et al 1982, ALS wasgivenintravenously in a daily dose of 120 mg/kg. Horse Ig levels in patients' sera were measured by hemagglutination inhibition, and the sera were also examined for lymphocytotoxic antibody, using a method described previously (Heyworth 1981).…”
Section: Attempts To Monitor the Dose Of Als In Human Subjectsmentioning
confidence: 99%